Dissociated deficits of anticipated and experienced regret in at-risk suicidal individuals - Ai, Hui; Duan, Lian; Huang, Lin; Luo, Yuejia; Aleman, André; Xu, Pengfei (Frontiers in Psychiatry, 2023)
Backgrounds: Decision-making deficits have been reported as trans-diagnostic characteristics of vulnerability to suicidal behaviors, independent of co-existing psychiatric disorders. Individuals with suicidal behaviors often regret their decisions of committing suicide and may have impairments in future-oriented processing. However, it is not clear how people with suicidal dispositions use future-oriented cognition and past experience of regret to guide decision-making. Here, we examined the processes of regret anticipation and experience in subclinical youth with and without suicidal ideation during value-based decision-making. Methods: Eighty young adults with suicidal ideation and seventy-nine healthy controls completed a computational counterfactual thinking task and self-reported measures of suicidal behaviors, depression, anxiety, impulsivity, rumination, hopelessness and childhood maltreatment. Results: Individuals with suicidal ideation showed diminished ability to anticipate regret compared to healthy controls. More specifically, suicidal ideators’ regret/relief experience was significantly different from healthy controls upon obtained outcomes, while their disappointment/pleasure experience was not significantly different from healthy controls. Conclusion: These findings suggest that young adults with suicidal ideation have difficulty to predict the consequence or the future value of their behaviors. Individuals with suicidal ideation showed impairments in value comparison and flat emotion upon retrospective rewards, while their responses to immediate rewards remain intact. Identifying the counterfactual decision-making characteristics of at-risk suicidal individuals may help to elucidate measurable markers of suicidal vulnerability and identify future intervention targets.